Valorization of Ahlat Stone Wastes in the Production of Ceramic Tiles: Physical-Mechanical Properties. Issue 4 (2nd October 2022) - Ercioglu-Akdogan, Nihan
Abstract : Ignimbrites (Ahlat Stone) with macro and micro-sized pores possessing independent of each other are volcanic rocks. It is mainly used as a building material because of its excellent insulation and easy to form material. The present study is aimed at producing floor tile which incorporated Ahlat stone as an alternative raw material for the ceramic industry. The effects of the increasing amount of Ahlat stone (1, 3 and 5 wt%) in the recipes on slurry rheology, physical properties of ceramic tiles, and sintering were studied. Chemical components of raw materials and Ahlat stone were determined using X-ray fluorescence spectroscopy and accordingly the recipes were created. The surface morphology of tiles was scanned using scanning electron microscope. When 3% Ahlat stone was added to the recipe, the flexural strength was calculated as 540 kgf.cm −2 . This value is 22% higher than the value which is specified in the TSE standards. Therefore, tiles with a longer lifetime and more durability were developed. In addition, the increased amount of Ahlat stone in the recipe reduced the sintering temperature, thus energy saving was achieved during firing. GRAPHICAL ABSTRACT: UF0001